NOVI KONCEPTI NASTAVE RUKOMETA U ŠKOLAMA - Elvir Kazazović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Basic changes in sport methodology demands changes in teaching traditional sports in schools. Nowadays technical elements are not taught separately but through the game. Since the new sports follow the development of society, traditional sports are becoming less attractive. But there is also the danger of too much adjusting to short-la sting trends, so as the consequence, the fundamental sport characteristics are not taught properly. What follows is that hand ball is not taught and played in sport lessons in schools, and school competitions as well because trainers/teachers have noticed the collision of the aims of school sports. Students are also not interested to be taught handball because they learn the theory too much and do not play enough. In addition, weaker students do not have the chance to be the part of the game. It would be necessary to establish new teaching methods so that handball can become attraction for teachers and students again.